(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This thesis analyzes the issues of forming students’ creative and intellectual potential based on a competency-based approach to teaching English. The importance of the communicative approach in developing students’ creative thinking, independent decision-making, and intellectual activity is highlighted.